Image analysis for studying the behaviour of broilers exposed to artificial LED lighting - Garcia, R. G.; Santana, M. R S [UNESP]; Nääs, I. A.; Caldara, F. R.; Eyng, C.; Paz, I. C L A [UNESP] (My University, 2015)
The photoperiod length and the type of light may influence both growth and behaviour of reared birds. The aim of this study was to evaluate broilers' behaviour when exposed to different LED colours. The study was carried out using a total of 1,296 male and female broilers reared until they were 42 days old. Broilers were randomly distributed in a 2x3 factorial scheme, with two sexes and three light sources, using six treatments and four repetitions. 54 birds per experimental unit were used. Two LED light source colours were tested. Broilers were reared under blue (480 nm) and red (660 nm) monochromatic lights and fluorescent light (6500 K, 15 lx). Their behaviour was analysed by indirect monitoring using pictures and vídeo footage. Four video footages of 5 min each were taken in each treatment at 28, 35 and 42 d of grow-out, with a total of 72 sets of video footage. The behavioural repertoire was recorded as an ethogram. There was a correlation (P<0.05) between birds' age, sex and light source for eating, drinking, exploring and feather pecking behaviours. The highest frequency of behavioural values was obtained in birds exposed to fluorescent light (1.67 eating; 0.83 preening) and red LED (2.00 drinking; 0.54 foraging). Results showed that birds exposed to red LED light and a compact fluorescent lamp were more active than broilers exposed to blue LED.
Keywords: Light Emitting Diode; Poultry welfare; Vision